2021
DOI: 10.2215/cjn.18311120
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Requiring Dialysis and Incident Dialysis Patient Outcomes in US Outpatient Dialysis Facilities

Abstract: Background and Objectives: About 30% of patients with acute kidney injury (AKI) may require ongoing dialysis in the outpatient setting after hospital discharge. A 2017 CMS policy change allows Medicare beneficiaries with AKI requiring dialysis to receive outpatient treatment in dialysis facilities. Outcomes for these patients have not been reported. We compare patient characteristics and mortality among AKI dialysis patients and non-AKI incident dialysis patients. Design, setting, participants, and measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Whereas, only 19% of them recovered kidney function to the extent without the need of further dialysis. Furthermore, 16% of D-AKI patients died (7). In a study involving intensive care patients surviving D-AKI, the subsequent risk of ESRD for D-AKI patients was 8.5%, within 180 days following ICU admission, compared with 0.1% for non-D-AKI ICU patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, only 19% of them recovered kidney function to the extent without the need of further dialysis. Furthermore, 16% of D-AKI patients died (7). In a study involving intensive care patients surviving D-AKI, the subsequent risk of ESRD for D-AKI patients was 8.5%, within 180 days following ICU admission, compared with 0.1% for non-D-AKI ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dialysis-Requiring Acute Kidney Injury (D-AKI) is one of the most severe entities of AKI KDIGO stage 3 (6), with high rates of mortality and ESRD (7,8). A retrospective study found that 66% of D-AKI patients had no recovery in kidney function, and they required chronic dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of CJASN , Dahlerus et al (1) report the results of a retrospective cohort study using 2017 outpatient dialysis Medicare claims to examine patient characteristics and mortality in patients with dialysis-requiring AKI discharged to receive outpatient dialysis compared with the non-AKI incident dialysis population. The authors found that patients with dialysis-requiring AKI had more comorbidities documented.…”
mentioning
confidence: 99%
“…The study by Dahlerus et al (1) distinguishes itself from similar prior studies by being national in scope (whereas most prior outpatient dialysis-requiring AKI studies were on the basis of single-center or single–health care system data only). Another strength is the nonreliance on the Centers for Medicare & Medicaid Services (CMS) Medical Evidence 2728 Form to identify AKI.…”
mentioning
confidence: 99%
See 1 more Smart Citation